Novel luminescent techniques in aid of food quality, product development, and food processing. (December 2021) - Colaruotolo, Louis A.; Peters, Eric; Corradini, Maria G.
Graphical abstract: Highlights: Autofluorescence in foods is a source of valuable information. Better specificity, quantum yields and environmental sensitivity drive novel probe design. Rapid acquisition (<20 s) makes luminescence techniques suitable for real-time measurements. Micro-spectroscopy can map matrix heterogeneity and food component interactions. Super resolution microscopy surveys spatial and temporal changes in food microstructure. Abstract : Although luminescence is considered a fundamental technique to study molecular properties and functions of structural and bioactive components, its application to foods has been limited. Herein, we discuss how advances in probe characterization and design, instrumentation, and high-resolution techniques provide new approaches to scout undisturbed food matrices and assist in monitoring food safety and food quality attributes during processing and storage. The role of novel techniques in identifying mechanisms, interactions, and structural features responsible for (or conducive to) food stability, nutrient accessibility and desirable textural characteristics in food products is also discussed.